Fracture Properties of Recycled Concrete Reinforced with Nanosilica and Steel Fibers - Yonggui Wang; Xuetong Zhang (Advances in Materials Science and Engineering)
To promote the engineering application of recycled concrete, recycled concrete is modified by the addition of nanosilica (NS) and steel fibers (SF) to form NS and SF reinforced recycled concrete (NSFRC). The effects of the replacement rate and the SF and NS content on the fracture properties of recycled concrete (RC) are analyzed via a three-point bending test. The research shows that the fracture surface of the specimen is relatively flat when no SF are added. With an increase in the SF or NS content, the initial cracking load, initiation fracture toughness, instability load, and fracture energy of the NSFRC increase. The fracture properties of RC composites reinforced with SF and NS are better than those of RC reinforced with a single material. When 2% NS and 1.5% SF are added, the fracture properties reach a maximum value. The damage model established in this study can better reflect the stress-strain relationship of NSFRC during fracture.